Brainjacking in deep brain stimulation and autonomy - Pugh, Jonathan; Pycroft, Laurie; Sandberg, Anders; Aziz, Tipu; Savulescu, Julian (Ethics and information technology, 2018)
'Brainjacking’ refers to the exercise of unauthorized control of another’s electronic brain implant. Whilst the possibility of hacking a Brain–Computer Interface (BCI) has already been proven in both experimental and real-life settings, there is reason to believe that it will soon be possible to interfere with the software settings of the Implanted Pulse Generators (IPGs) that play a central role in Deep Brain Stimulation (DBS) systems. Whilst brainjacking raises ethical concerns pertaining to privacy and physical or psychological harm, we claim that the possibility of brainjacking DBS raises particularly profound concerns about individual autonomy, since the possibility of hacking such devices raises the prospect of third parties exerting influence over the neural circuits underpinning the subject’s cognitive, emotional and motivational states. However, although it seems natural to assume that brainjacking represents a profound threat to individual autonomy, we suggest that the implications of brainjacking for individual autonomy are complicated by the fact that technologies targeted by brainjacking often serve to enhance certain aspects of the user’s autonomy. The difficulty of ascertaining the implications of brainjacking DBS for individual autonomy is exacerbated by the varied understandings of autonomy in the neuroethical and philosophical literature. In this paper, we seek to bring some conceptual clarity to this area by mapping out some of the prominent views concerning the different dimension of autonomous agency, and the implications of brainjacking DBS for each dimension. Drawing on three hypothetical case studies, we show that there could plausibly be some circumstances in which brainjacking could potentially be carried out in ways that could serve to enhance certain dimensions of the target’s autonomy. Our analysis raises further questions about the power, scope, and necessity of obtaining prior consent in seeking to protect patient autonomy when directly interfering with their neural states, in particular in the context of self-regulating closed-loop stimulation devices.